High quality of diabetes care in Greenland since the launch of Steno Diabetes Center Greenland 2020 - geographical disparities need attention - Marie Balslev Backe; Marit Eika Jørgensen; Michael Lynge Pedersen (International Journal of Circumpolar Health, 2023)
ABSTRACTThe aim of this study was to estimate the prevalence of diagnosed diabetes in Greenland and evaluate quality of care according to sex, region and healthcare unit within regions. Data on all inhabitants registered with diabetes were extracted from the electronic medical record. We found a crude prevalence of diagnosed diabetes in the population aged ≥ 20 years to be 4.7%, and the prevalence of diabetes standardised to the WHO world population was 4.0%. Compared to males, a significantly higher proportion of females had mean glycated haemoglobin (HbA1c) level below 7% (68.9% vs. 57.5%) and blood pressure below 140/90 mmHg (83.4% vs. 73.5%). Regarding healthcare unit within regions, quality of care was higher in regional cities compared to smaller cities, concerning proportion of persons having blood pressure measured regularly (86.0% vs. 71.7%), urine tested for albuminuria (70.6% vs. 51.2%), receiving eye examination (86.9% vs. 79.5%) and foot examination (87.9% vs. 79.4%). In conclusion, the prevalence of diagnosed diabetes in Greenland is the highest reported yet. The overall quality of diabetes care was high and significantly improved compared to 2018. We observed geographical inequality in diabetes care and improvements in the quality of care in specific remote locations are necessary to minimise health care disparities.